ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI NIAT PERILAKU MENGGUNAKAN PERBANKAN DIGITAL PADA GENERASI Y DAN Z: PERAN MEDIASI EKSPEKTASI KINERJA DALAM MODEL UGT DAN UTAUT2 - Sekarwangi Larasati; Wahyu Meiranto (Diponegoro Journal of Accounting, 2026)
This study aims to analyze the factors influencing behavioral intentions and actual behavior regarding the use of digital banking services among Generation Y and Z in Indonesia. This study integrates the Uses and Gratifications Theory (UGT) and the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2), with performance expectations serving as a mediating variable. The variables used in this study include cognitive needs, affective needs, social needs, performance expectations, effort expectations, social influence, facilitating conditions, habits, hedonic motivation, perceived value, behavioral intention, and usage behavior.This study employs a quantitative approach using primary data collected through a questionnaire survey. The study sample consisted of 473 respondents who are users of digital banking services from Generations Y and Z in Indonesia. The collected data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS software. The use of this method aimed to test both direct and indirect relationships among variables in the research model.The results of the study indicate that cognitive needs have a positive effect on performance expectations and behavioral intentions, while affective needs have a positive effect on performance expectations, effort expectations, and behavioral intentions. Performance expectations were found to mediate the relationship between cognitive needs and affective needs and behavioral intentions. Additionally, social needs have a positive effect on social influence, and social influence has a positive effect on behavioral intentions. Performance expectations, effort expectations, facilitating conditions, habits, hedonistic motivation, and value of price also have a positive effect on behavioral intention. Furthermore, behavioral intention has a positive effect on the behavior of using digital banking.